Number of previous ankle sprains a latent risk factor for recurrent ankle sprain in young soccer players - Genki Futatsubashi; Syusaku Sasada; Hiroyuki Ohtsuka; Tomoyoshi Komiyama (Japanese Society of Physical Fitness and Sports Medicine, 2014)
In the present study, the aim was to determine whether a history of ankle sprain during the junior (JUN; age < 12 years) playing years of soccer players could predict the occurrence of ankle sprain in their junior youth (JY; age < 13, 14, and 15 years) playing years. Therefore, we administered a questionnaire survey to 1,361 players belonging to 28 JY soccer teams. Analyses of the participants' answers indicated that 57.0% of the players sustained ankle sprains during their JUN playing years and 64.0% of the players sustained ankle sprains during their JUN and JY playing years. Players with a history of ≥5 ankle sprains had a higher occurrence rate of sprains in their JY years as compared to players with no history of ankle sprains. The odds ratio (OR), calculated using logistic regression analysis based on the number of ankle sprains sustained during the JUN playing years, was highest for players with ≥5 sprains compared to those with 2 or 3 sprains during the JUN playing years. To reduce the occurrence rate of ankle sprains for players in the JY category, effective screening processes, prevention measures, and rehabilitation programs for ankle sprains during the JUN playing years should be established.